Nursing students' risk perceptions related to medication administration error: A qualitative study. (January 2022) - Roman Jones, Joanne; Boltz, Marie; Allen, Rachel; Van Haitsma, Kimberly; Leslie, Douglas
Abstract: Aim: The purpose of this study was to explore and describe pre-licensure nursing students' perceptions of risk for medication administration errors in fourth-year baccalaureate student nurses from three campuses at a large central Pennsylvania university. Background: Medication administration errors continue to be a significant safety concern in healthcare settings. Pre-licensure nursing education is a critical time period during which to have an impact on future medication administration practices. Perception of risk influences decision making and behavior, including nursing clinical decision making. Design: This descriptive, exploratory study involved a qualitative design. Methods: A thematic analysis of the qualitative data resulting from 60 individual, in-depth semi-structured interviews was conducted. Results: The participants offered rich, detailed narratives which revealed the following themes: (1) the nature of risk perceptions, (2) more opportunities to learn, (3) experiences with medication administration error, and (4) intrinsic characteristics influence errors. Conclusions: The findings provide a broad description of the nature of student nurse risk perceptions for future medication administration errors. Recommendations for nursing education practice and pedagogy include additional clinical experiences, modified pharmacology curricula and instruction, and expanded simulations involving medication administration error. Highlights: Student nurses described their risk perceptions of medication administration errors. Student nurses seek more opportunities to learn. Students perceived error experiences to influence planned professional behaviors. Student nurses detailed intrinsic characteristics that influence errors.